HADITS-HADITS POLITIK ABAD PERTENGAHAN ISLAM (Suatu Kajian Sosiologis) - Makrum Makrum (IAIN Pekalongan, 2009)
Prophet’s hadith has an important role in Islamic teaching. Therefore, a Muslim community, in Islamic medieval century, tried to use hadith to legitimize their group existence and interest, even though they had to fabricate hadith for it. Hadith fabrication, at the beginning, happened because of political problems during Ali bin Abi Thalid order era. In its progression, the appearance of those political hadiths is to give one thing with another to the groups that politically and theologically have extreme opinions.